Microeconometric analysis of earnings mobility of immigrants and ethnic minorities: evidence from the UK - Sayema H. Bidisha; Anupam Das; Adian A. McFarlane (Journal for Labour Market Research, 2013)
This paper analyzes intergenerational earnings mobility of immigrants and ethnic minorities in the UK. We use a two-sample technique and utilize the British Household Panel Survey for estimating the mobility coefficient. The estimation provides the evidence of differences in generational mobility based on immigration status and ethnic origin. Earnings of the native population tend to have a strong correlation with that of their fathers, a mobility coefficient of 0.34. However, for immigrants as well as ethnic minorities, the fathers' earnings have a smaller impact on childrens' earnings with a much lower coefficient estimate.
Keywords: 330; Einwanderer; ausländische Arbeitnehmer; Minderheiten; ethnische Gruppe; Intergenerationsmobilität; Lohnhöhe; soziale Mobilität; Einkommenshöhe; Großbritannien